2004
DOI: 10.1183/09031936.04.00013903
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis obliterans syndrome in popcorn production plant workers

Abstract: Following sentinel case recognition, an excess of fixed airways obstruction was found among current workers in a microwave popcorn plant associated with butter flavouring exposures.In order to characterise the clinical presentation of sentinel cases, the medical records of sentinel cases were reviewed, interviews conducted and serial spirometric testing performed.Cases worked in microwave popcorn production, and five of the nine cases had mixed flavourings. Most had never smoked or smoked minimally. Cases show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
179
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(185 citation statements)
references
References 17 publications
6
179
0
Order By: Relevance
“…22 It has been identified as a prominent volatile organic compound in air samples from microwave popcorn plants and flavoring manufacturing plants. 23,24 DA exposure through inhalation has been associated with a decline in respiratory function (characterized by a declined in FEV 1 ) and the development of bronchiolitis obliterans, a rare irreversible obstructive disease involving the respiratory bronchioles. Kreiss et al 13 evaluated 117 workers in a microwave popcorn production plant in Missouri and found that these workers had 2.6 times the expected rate of respiratory symptoms such as chronic cough and shortness of breath and 3.3 times the expected rate of airway obstruction.…”
Section: Toxicity Of Da and Apmentioning
confidence: 99%
“…22 It has been identified as a prominent volatile organic compound in air samples from microwave popcorn plants and flavoring manufacturing plants. 23,24 DA exposure through inhalation has been associated with a decline in respiratory function (characterized by a declined in FEV 1 ) and the development of bronchiolitis obliterans, a rare irreversible obstructive disease involving the respiratory bronchioles. Kreiss et al 13 evaluated 117 workers in a microwave popcorn production plant in Missouri and found that these workers had 2.6 times the expected rate of respiratory symptoms such as chronic cough and shortness of breath and 3.3 times the expected rate of airway obstruction.…”
Section: Toxicity Of Da and Apmentioning
confidence: 99%
“…2e4 In workers, high-resolution computed tomography scans demonstrated bronchial wall thickening in eight popcorn manufacturing workers, and two workers had biopsy findings consistent with constrictive bronchiolitis. 5 Additional cases of fixed airways obstruction were subsequently identified in workers exposed to diacetyl vapors in other workplaces; those workplaces involved microwave popcorn, coffee, chemical, and flavorings production. 6e9 Recently, workers in flavoring production were found to have an increased prevalence of restrictive lung disease, suggesting that the full spectrum of pulmonary function abnormalities associated with inhaling flavoring vapors may include restrictive as well as obstructive lung disease.…”
mentioning
confidence: 99%
“…For workers hired prior to the implementation of exposure controls, persistent symptoms and continued excessive declines in lung function might be a manifestation of the effects of previous higher exposures, or might be due to levels of exposure that were still too high. Two of the former worker index cases continued to have excessive declines in lung function many months to years after leaving the plant, 16 as did three current workers who participated in NIOSH surveys after they stopped working in microwave popcorn production. Because of this, it was important to evaluate new workers who were hired after exposures were controlled.…”
Section: Context Of Investigationmentioning
confidence: 99%
“…June 6, 2001 Flavoring cabinets. July 16,2001 Controller for heat on flavor tank. August 7, 2001 Intake for Rupp completed.…”
Section: February 2001mentioning
confidence: 99%